ANALISIS PERKEMBANGAN SNI BIDANG TEKSTIL DAN PRODUK TEKSTIL - Eddy Herjanto (JURNAL STANDARDISASI, 2007)
Textiles and textile products is one of the leading sectors in Indonesia export product. The development of the industry should be supported in order to maintain their position and to increase their competitiveness abroad. Indonesian National Standard (SNI) can be one of the useful factors as a reference in product quality as well as in facilitating trade. Therefore, the availability of good national standard is necessary. The aim of this research is to know market development of textiles industry and the availability of the SNI with respect to strengthening SNI on textiles industry supply-chain. The result showed that there was a gap on national standards availability among these industries, i.e. national standards of some of the textile products do not exist. Moreover, it is needed to increase the quality of most of the existing standards.